Resistance in Indian wheat and triticale against loose smut caused by Ustilago tritici - S.K. JAIN, S.K. PANT, INDU SHARMA, RITU BALA, V.L. MAJUMDAR and R.K. BANSAL, D.P. SINGH*, A.K. SHARMA, S.S. KARWASRA (Indian Phytopathology, 2017)
A total of 988 numbers of wheat and Triticale varieties and genotypes were evaluated against loose smut at hot spot locations, Almora in Northern hills zone, Ludhiana, Hisar and Durgapura in North Western plains zone of India under artificially inoculated conditions using local isolates of loose smut (Ustilago tritici) pathogen from 2007-08 to 2011-12 crop seasons. Ninety four genotypes and varieties of wheat and Triticale were found highly resistant (free from infection) whereas 20 genotypes and varieties were found resistant (0.1-5.0% infection) over years and locations. The wheat varieties, HS 277, KRL 210, MACS 2846, MACS 2971, VL 829 A-9-30-1, GW 1189, HD 4672, HI 8498, HI 8627, HI 8663, MPO 1215, NIDW 295, PDW 233, PDW 291, WH 896 NP 200 were highly resistant. These may be used for breeding for disease resistant as resistant donor parents and resistant wheat varieties may be deployment in disease endemic areas.